BOVINE BABESIOSIS PARTIALPURIFICATION AND CHARACTERIZATION OF BLOOD CULTUREDERIVED BABESIABOVIS - GIRAL, MARIA LUISA; GIRAL, JOSE; GIRAL, FRANCISCO (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, Laboratorio Bacteriología , CD MEXICO, DF, MEX, 1960)
Most textbooks state that cysts of I williamsi are frequently found, but that trophozoites are seldom seen The author presents the results of the examination of 100 samples each, normally passed or purged stools, finding that in both cases trophozoites
J ANIM SCI
Keywords: FATS, INSECTS, COMPOSITION, MELANOPLUS ATLANIS RILEY; CIENCIAS DE LA VIDA; BIOLOGIA MOLECULAR; BIOLOGIA MOLECULAR DE PLANTAS